2019
DOI: 10.1029/2019ja027392
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of the Middle Atmosphere Circulation and Stationary Planetary Waves on the Solar Activity Effects in the Thermosphere

Abstract: Using numerical simulations of the general atmospheric circulation during boreal winter, statistically confident evidences are obtained for the first time, demonstrating that changes in the solar activity (SA) in the thermosphere at heights above 100 km can influence propagation and reflection conditions for stationary planetary waves (SPWs) and can modify the middle atmosphere circulation below 100 km. A numerical mechanistic model simulating atmospheric circulation and SPWs at heights 0-300 km is used. To ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…The modified SPWs in the northern stratosphere before and during SSW (Stray et al, 2015;Gavrilov et al, 2018) can then propagate along the waveguides to the southern upper atmosphere. Laskar et al (2019) showed similar significant weakening (up to a reversal) of both the mean and residual meridional circulation at MLT heights during SSW observed in the winters of 2009/10 and 2012/13, causing temperature fluctuations in the stratosphere of both hemispheres. Larger velocity add-ons in the southern MLT region after SSW in Fig.…”
Section: Residual Circulation At the Different Ssw Stagesmentioning
confidence: 55%
“…The modified SPWs in the northern stratosphere before and during SSW (Stray et al, 2015;Gavrilov et al, 2018) can then propagate along the waveguides to the southern upper atmosphere. Laskar et al (2019) showed similar significant weakening (up to a reversal) of both the mean and residual meridional circulation at MLT heights during SSW observed in the winters of 2009/10 and 2012/13, causing temperature fluctuations in the stratosphere of both hemispheres. Larger velocity add-ons in the southern MLT region after SSW in Fig.…”
Section: Residual Circulation At the Different Ssw Stagesmentioning
confidence: 55%
“…Although many studies have been conducted on the responses of atmospheric circulation to solar activity, they focused on some kinds of atmospheric circulation in the middle and lower atmosphere or at specified latitude regions [40,41,43,44,46]. In this work, the responses of global atmospheric circulation from the ground to ~500 km to solar activity were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Kodera and Kuroda [40] suggested that solar activity can change the balance between the dynamically and radiatively controlled states, which can influence stratopause circulation. Koval et al [41] used a general atmospheric circulation model to demonstrate that changes in solar activity can modify the middle atmospheric circulation. Vasilyeva et al [42] discussed the possible effects of solar activity on the tropospheric temperature regime based on the analysis of the tropospheric temperature regime in the northern and southern hemispheres in 1948-2006.…”
Section: Introductionmentioning
confidence: 99%
“…The incoming solar radiation and heating depend on the SA, which undergoes cyclic changes with a period of about 11 years (see e.g., [8]). In the study [9], it was shown that SA changes in the thermosphere can significantly influence middle-atmosphere circulation and amplitudes of quasi-stationary PWs. Wave reflection in the lower thermosphere may also influence the circulation of the middle atmosphere (e.g., [9,10]).…”
Section: Introductionmentioning
confidence: 99%
“…In the study [9], it was shown that SA changes in the thermosphere can significantly influence middle-atmosphere circulation and amplitudes of quasi-stationary PWs. Wave reflection in the lower thermosphere may also influence the circulation of the middle atmosphere (e.g., [9,10]). Among the reasons for PW reflection at thermospheric heights can be significant temperature and wind gradients.…”
Section: Introductionmentioning
confidence: 99%